A Community Deliberative Polling Event: The Economic Impact of Walmart - Christopher Latimer; Karen Hempson; J. Richard Kendrick, Jr (The University of Alabama, 2022)
This article presents the results of a deliberative poll in which members from the local community and college students from SUNY Cortland discussed the economic impact of Walmart on a small town. We review the literature concerning deliberative polling and describe the process of the deliberative polling event. Our examination of the data focuses on net changes in the participants' opinions and gross changes in the participants' opinions. We discuss the trends and implications of the opinion shifts and outline future research. The results illustrate that the process of deliberation affects changes in attitude items at both the individual and group level.